Central importance of emotional and quality-of-life outcomes in the public's perception of face transplantation. Issue 10 (5th May 2021) - Murphy, D C; Hoyle, V; Saleh, D; Rees, J; Bound Alberti, F
Abstract: Background: Face transplantation is a surgical innovation to manage people with severely interrupted facial function and form. How the public perceive face transplantation and its potential implications for the recipient, donor, and society is unclear. The aim of this study was to understand the public perception of face transplantation, including when it is appropriate, what information is required to feel adequately informed, and which factors influence a person's willingness to donate their face. Methods: This was a nationwide survey of participants representative of the GB public. A quantitative analysis was performed. Free-text qualitative responses were coded with thematic content analysis and a narrative analysis was constructed. Results: The survey included 2122 participants. Face transplantation was considered worth the potential risks if it improved an individual's quality of life, gave them a 'normal life', and/or increased their confidence and social interaction. Respondents were worried about the impact face transplantation might have on donor families, especially recipient families adapting to the identity of the donor. Respondents most concerned about the concept of face transplantation were aged at least 55 years (χ 2 (4) = 38.9, P < 0.001), women (χ 2 (1) = 19.8, P < 0.001), and Indian/Asian (χ 2 (4) = 11.9, P = 0.016). Conclusion: The public perceive emotional and psychological outcomes as equally as important as, or more important than, surgical outcomes when determining the appropriateness of face transplantation. Future research should focus on measuring and describing emotional and psychological outcomes after face transplantation. Abstract : This article explores public perceptions of face transplants, and highlights the importance of psychosocial as well as surgical outcomes. It shows how important qualitative research is in understanding and evaluating facial transplantation as a form of vascular composite allograft. It also highlights the importance of consulting the public, and facial difference communities, in order to account for lived experience and beliefs about face transplants.